Radiation-induced opticochiasmatic glioblastoma multiforme following conventional radiotherapy for Cushing's disease. (August 2014) - Sarkar, Sauradeep; Rajaratnam, Simon; Backianathan, Selvamani; Chacko, Geeta; Chacko, Ari George
Abstract We report the rare occurrence of an opticochiasmatic glioblastoma multiforme 6 years following conventional radiotherapy for Cushing's disease. This article highlights the risks of collateral damage to the optic apparatus when irradiating the sellar region.